Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.

Ratiometric detection of Cr3+ and Hg2+ by a naphthalimide-rhodamine based fluorescent probe - Mahato, Prasenjit; Saha, Sukdeb; Suresh, E.; Liddo, Rosa Di; Parnigotto, Pier Paolo; Conconi, Maria Teresa; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2012)
Newly synthesized rhodamine derivatives, L1 and L2, are found to bind specifically to Hg2+ or Cr3+ in presence of large excess of other competing ions with associated changes in their optical and fluorescence spectral behavior. These spectral changes are significant enough in the visible region of the spectrum and thus, allow the visual detection. For L1, the detection limit is even lower than the permissible [Cr3+] or [Hg2+] in drinking water as per standard U.S. EPA norms; while the receptor, L2 could be used as a ratiometric sensor for detection of Cr3+ and Hg2+ based on the resonance energy transfer (RET) process involving the donor naphthalimide and the acceptor Cr3+/Hg2+-bound xanthene fragment. Studies reveal that these two reagents could be used for recognition and sensing of Hg2+/Cr3+. Further, confocal laser microscopic studies confirmed that the reagent L2 could also be used as an imaging probe for detection of uptake of these ions in A431 cells.

Role of metal ion in specific recognition of pyrophosphate ion under physiological conditions and hydrolysis of the phosphoester linkage by alkaline phosphatase - Das, Priyadip; Chandar, Nellore Bhanu; Chourey, Shishir; Agarwalla, Hridesh; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2013)
Complexes synthesized from Zn(II), Cu(II), and Cd(II), using a dipicolyl amine derivative (L), showed unique specificity toward pyrophosphate ion (PPi or P4O74-) among all other common anionic analytes, including different biologically significant phosphate ion (PO43-, H2PO42-) or phosphate-ion-based nucleotides, such as AMP, ADP, ATP, and CTP. However, the relative affinities of PPi toward these three metal complexes were found to vary and follow the order K-a(L.Zn-PPi) > are given in units of (L.Cu-PPi)(a) >= K-a(L.Cd-PPi). Luminescence responses of the receptor L were substantial on binding to Zn2+ and Cd2+, while relatively a much smaller luminescence response was observed in the presence of Cu2+. Luminescence responses of L.M-PPi (M is Zn2+, Cd2+, and Cu2+) were further modified on binding to the PPi ion. This could be utilized for quantitative detection of PPi in physiological condition as well as for developing a real time ``turn-on'' (for L.Zn and L.Cu) and ``turn-off'' (for L.Cd) fluorescence assay for evaluating the enzymatic activity of alkaline phosphatase (ALP). Experimental results revealed how the subtle differences in the binding affinities between PPi and M in L.M (M is Zn2+, Cd2+, and Cu2+), could influence the cleavage of the phosphoester linkage in PPi by ALP. The DFT calculations further revealed that the hydrolytic cleavage of the metal ion coordinated phosphoester bond is kinetically faster than that for free PPi and thus, rationalized the observed difference in the cleavage of the phosphoester bond by an important mammalian enzyme such as ALP in the presence of different metal complexes.